2021
DOI: 10.1371/journal.pone.0256813
|View full text |Cite
|
Sign up to set email alerts
|

Resilient SARS-CoV-2 diagnostics workflows including viral heat inactivation

Abstract: There is a worldwide need for reagents to perform SARS-CoV-2 detection. Some laboratories have implemented kit-free protocols, but many others do not have the capacity to develop these and/or perform manual processing. We provide multiple workflows for SARS-CoV-2 nucleic acid detection in clinical samples by comparing several commercially available RNA extraction methods: QIAamp Viral RNA Mini Kit (QIAgen), RNAdvance Blood/Viral (Beckman) and Mag-Bind Viral DNA/RNA 96 Kit (Omega Bio-tek). We also compared One-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…We therefore optimised sample preparation to allow rapid, sensitive, and repeatable testing directly from saliva without purification of RNA (direct RT-LAMP). To avoid time-consuming RNA extractions, we trialled a range of different heat inactivation protocols 21,22 and saliva collection solutions 23,24 , all of which have been found to improve sensitivity in RT-PCR or RT-LAMP assays. However, we adopted a protocol in which fresh or frozen saliva was diluted at least 1 in 4 in AviSal Sample Collection Buffer (Hayat Genetics), followed by virus heat inactivation at 95°C for 10 minutes.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore optimised sample preparation to allow rapid, sensitive, and repeatable testing directly from saliva without purification of RNA (direct RT-LAMP). To avoid time-consuming RNA extractions, we trialled a range of different heat inactivation protocols 21,22 and saliva collection solutions 23,24 , all of which have been found to improve sensitivity in RT-PCR or RT-LAMP assays. However, we adopted a protocol in which fresh or frozen saliva was diluted at least 1 in 4 in AviSal Sample Collection Buffer (Hayat Genetics), followed by virus heat inactivation at 95°C for 10 minutes.…”
Section: Resultsmentioning
confidence: 99%
“…This is the first report of a high-throughput HI protocol for SARS-CoV-2 testing that is performed on UN733 packaged OP/NP swab samples in bulk. Although the use of heat is an effective means of SARS-CoV-2 inactivation 8 , 11 13 , 23 – 25 , COVID-19 testing laboratories have relied on chemical lysis during RNA extraction for viral inactivation. Chemical lysis is highly effective mechanism of virus inactivation 26 , 27 , but requires handling of potentially viable SARS-CoV-2 samples that represents a risk to operators.…”
Section: Discussionmentioning
confidence: 99%
“…A critical aspect of this work has been an experimental demonstration of virus inactivation using the bulk HI protocol on mock OP/NP swab samples. Insufficient exposure at the required temperature could result in incomplete viral inactivation 13 , 28 which is especially important for samples with high viral load 11 , 12 , 29 . In addition our bulk HI protocol employs wet heat as opposed to dry heat as previously used 30 , which can lead to evaporation and incomplete viral inactivation 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reverse transcriptase enzyme can then assemble the complementary DNA strand (cDNA) that is amplified subsequently by the DNA polymerase. In this way, Lista et al 30 reported that qRT-PCR amplifies the N1 and N2 genetic sequences of SARS-CoV-2 inactivated or not by heating similarly, even leading to indistinguishable Ct values.…”
mentioning
confidence: 99%